Marketing Politik Calon Gubernur Kalimantan Tengah 2024: Analisis Konten Instagram: Political Marketing of Central Kalimantan Governor Candidate 2024: Instagram Content Analysis - Firdaus, Aldi; Muksin, Nani Nurani (Anterior Jurnal, 2025)
This research was carried out to analyze the political marketing of the 2024 Central Kalimantan governor candidates, namely Willy Midel Yoseph, Nadalsyah Koyem, Agustiar Sabran, and Abdul Razak on Instagram social media. This research uses political marketing strategy theory which includes push, pull, and pass marketing which is applied to social media (Computer Mediated Communication) which consists of Selective Self-Presentation, Verbal clues or text messages, and Many-to-many communication. Data was obtained by conducting content analysis on Instagram social media accounts. The results of the research show that the four candidates for governor of Central Kalimantan in 2024 have delivered repeated messages on social media using informative and educative methods. In general, the political communication marketing strategy implemented is quite optimal because every candidate's post implements it, as seen on Push Marketing, First Candidate Willy Midel Yoseph created promotional content, Second Candidate Nadalsyah Koyem created collaborative content with Influencers, Third Candidate Agustiar Sabran created visual campaign content, and Fourth Candidate Abdul Razak created social activity content. At Pull Marketing, the four candidates uttered slogans explaining their vision and mission work programs, the first candidate, namely Tuh Iye Kalteng Harmonis, the second candidate, namely Kalteng Hebat, the third candidate, namely Kalteng Berkah Kalteng Maju, and the fourth candidate, is Kalteng Amanah. At Marketing Pass, the first candidate was promoted by the public, the second candidate was promoted by influencers, the third candidate was promoted by political figures, and the fourth candidate was promoted by community figures.